Question

# If G(x) = 3x + 1, then G^-1(1) is

Answer

One possible method for solving this problem is to first determine the inverse function of G(x). Alternatively, a faster approach is to examine G(x) = 3x + 1 and solve for the x value when y = 1: 1 = 3x + 1. From this equation, we can deduce that x equals 0. If the point (0, 1) satisfies G(x) = 3x + 1, then the point (1, 0) satisfies the inverse function of G(x) = 3x + 1. Therefore, the output of the inverse function when the input is 1 is 0. To accomplish this, we need to first substitute "G(x)" with "y". Next, we solve for x in the resulting equation. Then, we switch the places of x and y and replace y with G(x). Finally, we substitute "1" for "x".